2000
DOI: 10.1093/jnci/92.22.1831
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Cigarette Smoking, Lifestyle Factors, and Microsatellite Instability in Colon Tumors

Abstract: This study suggests that smoking cigarettes statistically significantly contributes to MSI in colon tumors. We estimate that approximately 21% of MSI in colon tumors may be attributable to cigarette smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
239
2
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(263 citation statements)
references
References 15 publications
19
239
2
3
Order By: Relevance
“…In the U.S., two small studies reported microsatellite instability in 16.9% 36 and 19.0% 37 of Latinos. In Puerto Rico, a larger retrospective study investigated an unselected group of Latino patients with CRC, on whom IHC staining of only two MMR proteins (MLH1 and MSH2) was performed 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the U.S., two small studies reported microsatellite instability in 16.9% 36 and 19.0% 37 of Latinos. In Puerto Rico, a larger retrospective study investigated an unselected group of Latino patients with CRC, on whom IHC staining of only two MMR proteins (MLH1 and MSH2) was performed 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Some have hypothesized that this finding may reflect differences in environmental and lifestyle factors between Latinos and other populations. For example, MSI-H CRC has been associated with tobacco use 36, 38 , which is less prevalent in Latinos compared to other populations 39 ; and high body-mass-index, which is more common in Latinos, is associated with microsatellite stable CRC tumors 40 . Further studies are needed to investigate these hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…Initial analyses of the relationships between microsatellite instability determined by either the panel of 10 tetranucleotides, BAT-26 or TGF␤RII in addition to various clinical and molecular features, gave nearly identical results regardless of the way instability was measured. 6 To simplify subsequent analyses we therefore combined these primer sets into a panel of 12 and scored a tumor as unstable if it was unstable with the panel of 10 tetranucleotides (as defined above), BAT-26 or TGF␤RII. Any associations detected in this way were then further defined by considering instability results with each of these 3 measures separately.…”
Section: Msimentioning
confidence: 99%
“…5 In our previous evaluation of lifestyle factors associated with MSI we found that cigarette smoking is specifically associated with MSI tumors, whereas other factors such as physical activity, body size, and use of aspirin and non-steroidal anti-inflammatory drugs appear to be related equally to MSIϩ and MSIϪ tumors. 6 Although dietary factors, to our knowledge, have not been examined with MSI in tumors, it is reasonable to hypothesize that components of diet, especially those that may be influenced by cigarette smoking, could influence development of unstable tumors. Alcohol could lead to unstable tumors independently or in combination with cigarette smoking.…”
mentioning
confidence: 99%
“…Perhaps more important, another 10 -15% of sporadic colorectal carcinoma cases are reportedly caused by the epigenetic silencing of the hMLH1 gene. Inappropriate silencing of the hMLH1 gene occurs through an incompletely understood mechanism in colonic tissues, appears to be influenced by age and, possibly, certain lifestyles or behaviors, 5 and appears to be the consequence of a genomewide phenomenon referred to as the CpG island methylator phenotype (CIMP). 6 Not surprisingly, epigenetic silencing of critical genes (such as those in the DNA MMR system) also occurs as a mechanism by which tumors develop in other organs.…”
mentioning
confidence: 99%